Linking restoration and sustainable wood fuel initiatives in Sahelian Cameroon - Sonwa, D.J.; Awono, A.; Essamba à Rim, L.F.; Tabi Eckebil, P.P. (2020)
Cameroon’s commitment to the AFR100 initiative to restore 12 million hectares of degraded land puts emphasis on the country’s three dry northern regions. One quarter of this commitment is supposed to take place in the Far North Region. The highest degradation of this region has clear impacts on livelihoods; in addition, the dependence of local communities, internally displaced people and refugees on unsustainable wood fuel collection contributes to further degradation.